Examining the benefits of audience integration: Does sharing of or commenting on online news enhance the loyalty of online readers?. Issue 5 (3rd July 2016) - Lischka, Juliane A.; Messerli, Michael
Abstract : This study investigates whether sharing of or commenting on online news enhances loyalty toward online news outlets. We identify two mediators of audience integration and loyalty: satisfaction and trust, which are measured by attitudinal attributions toward a news outlet. Loyalty is measured by frequently and exclusively using an online news outlet and an absent willingness to change to another online news outlet in the future. The relations between audience integration, satisfaction, trust, and loyalty are estimated with a mediation model. Results from an online survey with N = 1825 Swiss online news users reveal small but significant effects of sharing and commenting quantities on loyalty. Sharing tends to increase satisfaction, which in turn enhances loyalty. In contrast, commenting deteriorates satisfaction and trust, but directly improves loyalty. Overall, sharing and commenting slightly increase loyalty. In conclusion, sharing has a small, positive attitudinal relationship-building capacity for online news outlets, whereas commenting does not. Nonetheless, commenting features should not be abandoned by news outlets.